1999
DOI: 10.1523/jneurosci.19-08-02996.1999
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of p53-Dependent Caspase Activation to Neuronal Cell Death Declines with Neuronal Maturation

Abstract: Caspases play a pivotal role in neuronal cell death during development and after trophic factor withdrawal. However, the mechanisms regulating caspase activity and the role played by caspase activation in response to neuronal injury is poorly understood. The tumor suppressor gene p53 has been implicated in the loss of neuronal viability caused by excitotoxic and DNA damaging agents. In the present study we determined if p53-mediated neuronal cell death required caspase activation. DNA damage increased caspase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 75 publications
8
80
0
Order By: Relevance
“…27 In the same way, RARaÀ/À mice exhibit caspase-independent spermatid loss. 28 Late differentiating male germ cells share similarities with various postmitotic/terminally differentiating models of caspase-independent cell death: p53-expressing or NMDAtreated neurons, 17,18 ischemic mature brain, 29 light-injured mature photoreceptor cells 19 or differentiating PC12 cells. 30 So in terminally maturing cells, calpain activation bypasses an inhibition or a block in the caspase pathway generally related to a decrease in apoptotic effectors like Apaf1 or caspase-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In the same way, RARaÀ/À mice exhibit caspase-independent spermatid loss. 28 Late differentiating male germ cells share similarities with various postmitotic/terminally differentiating models of caspase-independent cell death: p53-expressing or NMDAtreated neurons, 17,18 ischemic mature brain, 29 light-injured mature photoreceptor cells 19 or differentiating PC12 cells. 30 So in terminally maturing cells, calpain activation bypasses an inhibition or a block in the caspase pathway generally related to a decrease in apoptotic effectors like Apaf1 or caspase-3.…”
Section: Discussionmentioning
confidence: 99%
“…These ubiquitous enzymes are involved (i) in testicular cell loss in ischemia/reperfusion models, 6 and (ii) in several models of postmitotic, differentiating cell death. [17][18][19] Calpain 2 mRNAs were observed at all differentiation stages of normal spermatogenesis without any modification in transgenic cells (Figure 7a). By contrast, calpain 1 mRNAs were only detected in normal SP cells and spermatocytes II.…”
Section: Calpains Are the Main Protease Effectors Of Death In Mtp53 Gmentioning
confidence: 94%
“…However, Eizenberg et al (1996) propose that p53 has an importance during brain development in directing progenitors toward either apoptosis or differentiation. p53 plays a key role in genotoxic stress-mediated apoptosis and G1 cell cycle arrest in many cell types including neural cells (Slack et al, 1996;Jordan et al, 1997;Komarova et al, 1997;Levine, 1997;Herzog et al, 1998;Xiang et al, 1998;Johnson et al, 1999;Chao et al, 2000;Chong et al, 2000;Chow et al, 2000;Miller et al, 2000;Bargonetti and Manfredi, 2002). Several reports have shown that, in vivo, g-irradiation preferentially induces apoptosis in undifferentiated multipotent precursors localized in subependyma zone, subventricular zone and subgranular zone of dentate gyrus of the brain of adult mice (Herzog et al, 1998;Chow et al, 2000;Lee et al, 2001;Uberti et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indeed demonstrated that p53 is required for caspase activation in response to genotoxic stress. 69,96,129,140 These findings suggest that some forms of neuronal injury invoke a common pathway involving signal transduction through p53, Bax, mitochondrial dysfunction, cytochrome c release and caspase activation. However, other forms of injury have been shown to induce neuronal cell death by stimulating Bax translocation and caspase activation independently of p53.…”
Section: Mechanism Of P53-mediated Cell Death In Neuronsmentioning
confidence: 95%
“…Caspase-3 activation is required for p53-dependent cell death in cerebellar granule neurons in response to ionizing radiation 96 consistent with results obtained in nonneuronal cells. 139,142 ± 144 However, specific peptide inhibitors of caspases (zVAD-fmk, zDEVD-fmk and BAF) did not protect hippocampal and cortical neurons from p53-dependent cell death induced by radiation, 71 glutamate 72 or camptothecin-treatment 140 when the neuronal cultures were established from postnatal animals as opposed to embryos. In addition, adenovirus-mediated overexpression of p53 promoted neuronal cell death but did not induce caspase activity in postnatal cortical neurons.…”
Section: Mechanism Of P53-mediated Cell Death In Neuronsmentioning
confidence: 99%